Effect of Maternal Colonization with History of Prolonged Rupture of Membrane on Neonatal Colonization and Early Onset Sepsis - M. Hanif Memon; Shahina Hanif; Farhan Saeed; Muhammad Iqbal; Muhammad Athar Khan; Fatima Siraj; Aisha (KARACHI MEDICAL AND DENTAL COLLEGE, 2020)
Abstract Objective: To determine the effect of maternal colonization with history of PROM on neonatal colonization and early-onset sepsis. Methods: A descriptive cross-sectional study was carried out at a single tertiary care hospital of Karachi from June 1st 2018 to May 31st 2019. A total of 155 patients' full-term new-borns between 37 to 41 weeks of gestation with a history of rupture of membranes more than 18 hours duration was selected by convenience sampling method. A high vaginal swab was collected from all full-term pregnant women with a history of PROM. After delivery of their new-borns, all babies were kept in the nursery under closed observation for 72 hours duration and their blood cultures, CRP (C- Reactive Protein) and CBC (complete blood count) was sent within 24 hours of delivery. Results: In our study, out of 155 PROM cases 58 (37.4) were growth positive and 50 (32.3) neonates had positive blood C/S at delivery. Out of 58 cases with suspected growth positive PROM mothers 51 had gram-negative organisms in HVS while only 7 mothers were gram-positive in HVS. Of all neonates with positive blood C/S at delivery 44 cases were gram-negative organisms in their blood. Conclusion: In our study organisms found in a high vaginal swab of the mother are similar to the organisms found in the blood culture of their new-born with early-onset sepsis.